2001
DOI: 10.1093/ije/30.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Are coffee and tea consumption associated with urinary tract cancer risk? A systematic review and meta-analysis

Abstract: In accordance with earlier reviews, we found that coffee consumption increases the risk of urinary tract cancer by approximately 20%. The consumption of tea seems not to be related to an increased risk of urinary tract cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 68 publications
2
45
1
3
Order By: Relevance
“…These study characteristics were used to evaluate sources of variation in effect estimates. All articles were independently scored by three reviewers (AJ, MZ, EF) similar to an earlier approach [28]. Disagreements were solved in consensus meetings.…”
Section: Methodsmentioning
confidence: 99%
“…These study characteristics were used to evaluate sources of variation in effect estimates. All articles were independently scored by three reviewers (AJ, MZ, EF) similar to an earlier approach [28]. Disagreements were solved in consensus meetings.…”
Section: Methodsmentioning
confidence: 99%
“…Coffee consumption and cancer of the urinary track was systematically reviewed in 2001 (48). The authors incorporated data on adjusted summary ORs from 16 studies on men and 12 on women.…”
Section: Bladder Cancermentioning
confidence: 99%
“…On the basis of currently available evidence, coffee consumption probably has no relationship with the risk of pancreatic, ovarian, renal, thyroid or prostate cancer. However, seven reviews located on urinary tract or bladder cancer reported possible slight increased risks with coffee consumption (12,13,(21)(22)(23)(24)(25) . While two systematic reviews calculated increased risks of approximately 20 % (23) and 26 % (25) , a European-based review found an increased risk only for drinkers of 10 cups or more per d (22) .…”
Section: Cancersmentioning
confidence: 99%